Diverse immune functions of hemocyanins - Coates, Christopher J.; Nairn, Jacqueline (Developmental and comparative immunology, 2014)
•Hemocyanin is a multifunctional protein.•Hemocyanins may aid disease resistance in cultured shellfish.•Hemocyanin and hemoglobin release antimicrobial peptides.•Structure–function relationship of hemocyanins. Substantial evidence gathered recently has revealed the multiple functionalities of hemocyanin. Contrary to previous claims that this ancient protein is involved solely in oxygen transport within the hemolymph of invertebrates, hemocyanin and hemocyanin-derived peptides have been linked to key aspects of innate immunity, in particular, antiviral and phenoloxidase-like activities. Both phenoloxidase and hemocyanin belong to the family of type-3 copper proteins and share a high degree of sequence homology. While the importance of phenoloxidase in immunity and development is well characterised, the contribution of hemocyanin to biological defence systems within invertebrates is not recognised widely. This review focusses on the conversion of hemocyanin into a phenoloxidase-like enzyme and the array of hemocyanin-derived immune responses documented to date.